1991
DOI: 10.1016/0006-3223(91)90004-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of neuroleptic treatment on polysomnographic measures in schizophrenia

Abstract: To study the effects of neuroleptic therapy on sleep EEG variables in schizophrenia, as well as the clinical correlates of these variables, we performed polysomnographic (PSG) studies on 14 schizophrenic inpatients before and during neuroleptic therapy. Sleep continuity measures improved after 3 weeks of neuroleptic therapy, showing decreased sleep latency and improved sleep efficiency. REM latency increased with treatment, although half the patients continued to exhibit REM latencies less than 60 min. Other s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 18 publications
0
25
0
1
Order By: Relevance
“…In healthy controls, 10-mg olanzapine increased the REM latency but decreased REM sleep time (16)(17)(18) via an antagonistic effect on muscarinic cholinergic receptors. Previous studies have not found a significant increase in REM latency in schizophrenic patients receiving haloperidol (27), but acute administration of olanzapine to schizophrenics produced a significant increase in REM density (30). The anticholinergic effects of olanzapine may predict the decrease of REM activity and REM density in electroencephalogram sleep records.…”
Section: Discussionmentioning
confidence: 95%
“…In healthy controls, 10-mg olanzapine increased the REM latency but decreased REM sleep time (16)(17)(18) via an antagonistic effect on muscarinic cholinergic receptors. Previous studies have not found a significant increase in REM latency in schizophrenic patients receiving haloperidol (27), but acute administration of olanzapine to schizophrenics produced a significant increase in REM density (30). The anticholinergic effects of olanzapine may predict the decrease of REM activity and REM density in electroencephalogram sleep records.…”
Section: Discussionmentioning
confidence: 95%
“…Subchronic treatment of patients suffering from schizophrenia with typical antipsychotics increases TST and sleep efficiency and reduces sleep latency in most of the studies but leaves percentage sleep stage 2 and REM unchanged (Taylor et al 1991;Wetter et al 1996;Maixner et al 1998). …”
Section: Discussionmentioning
confidence: 97%
“…Considering known cholinergic effects on REM latency and other sleep measures Gillin and Sitaram 1984), these data are consistent with the hypothesis of increased cholinergic activity in schizophrenia and its implication in the production of negative symptoms. In related studies (Taylor et al 1991;Maixner et al 1998;Tandon 1997), we observed that polysomnographic measures partially normalized following antipsychotic treatment (with neuroleptics, clozapine, and risperidone). Assuming that increased cholinergic activity partly underlies polysomnographic abnormalities in schizophrenia at drug-free baseline, these data may indicate a trend for increased cholinergic activity to partially normalize with neuroleptic therapy (Figure 1) (Tandon and Greden 1989;Tandon et al 1990a).…”
Section: In Vivo Measurement Of Central Cholinergic Activitymentioning
confidence: 99%